SOSIALISASI KESADARAN LINGKUNGAN DIFERENSIASI MANGROVE BERBASIS PjBL STEAM PADA PESERTA DIDIK DI PESISIR PULAU AMBON - Papilaya, Pamella Mercy; Tuapattinaya, Prelly M J (PAKEM : Jurnal Pengabdian Kepada Masyarakat, 2023)
The socialization of mangrove differentiated environmental awareness based on PjBL STEAM aims to produce high-order thinking skills oriented products by implementing them in learning. In addition to producing art products about mangrove plants. This activity was motivated by the teacher's limitations in empowering participants' awareness of differentiated environment because the design and learning patterns were still traditional based on low-level cognitive achievement. On the other hand, teachers are limited to participating in various activities to support the improvement of their performance and profession including information on developing issues related to the environment as well as competencies and skills in teaching students according to the needs of the times. This activity also aims to introduce teachers to ideal pedagogical competencies in line with the demands of globalization, especially in cultivating and training creative thinking skills about environmental issues for elementary education students.